THE IMPACT OF SOCIO-ECONOMIC BACKGROUND ON THE LIFE SKILLS OF SPORTS AND NON-SPORTS STUDENTS - Syarifatunnisa, Syarifatunnisa; Anira, Anira (ASEAN Journal of Sport for Development and Peace, 2021)
Socio-economic background (SEB) is one of the factors that cause bullying in schools. Several studies have shown learning life skills (LS) to deal with these issues. This study aims to examine the impact of SEB on LS in sports and non-sports students. The sample of this study was 109 students (sports students = 57 and non-sports students = 55) with an age range of 19-21 years who were students of the Universitas Pendidikan Indonesia. Sampling was taken by the intake class method—data collection using the LSSS (Life Skills Scale for Sports) instrument. The research is a comparative causal method with test analysis using the Independent Sample T-Test, Kruskal-Wallis Test, and One-way ANOVA. The results of this study show a significant difference between the life skills of sports and non-sports students (F = 0.138, p = 0.031). There is a significant difference between sports and non-sports students' LS based on socio-economic status (lower class, middle class, and upper class), with p = 0.000 for sports students and p = 0.028 for non-sports students. This study reveals that the LS of sports students is higher than non-sports students.